Factors Causing Disparity in Judges' Decisions in Narcotics Cases - Rahayu, Dessy; Siregar, Taufik; Amal, Ridha Haykal (Journal La Sociale, 2025)
This study aims to analyze the factors that cause the disparity in judges' decisions in narcotics cases in Indonesia. The disparity of judges' decisions refers to the difference in the results of decisions between one judge and another in similar cases. The factors that cause this disparity can come from various aspects, both internal and external, that affect the objectivity of the judge in giving the verdict. Some of the factors found include differences in interpretation of the law, the social and cultural background of judges, as well as pressure from the public and the media. In addition, the subjectivity of judges and inconsistency in the application of legal provisions also play a role in creating injustice in the criminal justice system. This study uses a qualitative research method with a literature study approach and interviews with legal practitioners. The results of the study show that the disparity in judges' decisions in narcotics cases can be minimized by having clear standard operating procedures (SOPs), increasing the capacity of judges in understanding narcotics cases, and providing more intensive professional ethics training. The study also suggests the need for tighter supervision of judges' decisions to ensure that every decision taken is in accordance with the principles of justice and applicable law.